Unveiling a Virulence-Regulating Mechanism in Aeromonas hydrophila: a Quantitative Exoproteomic Analysis of an AraC-Like Protein - Zhang, Lishan; Sun, Lina; Srinivasan, Ramanathan; Lin, Meizhen; Gong, Lanqing; Lin, Xiangmin (Frontiers in Immunology, 2023)
Bacterial AraC is a transcription factor family that initiates transcription by recruiting RNA polymerase to the promoter and directly regulate various bacterial phenotypes. It also directly regulates various bacterial phenotypes. However, how this transcription factor regulates bacterial virulence and affects host immunity is still largely unknown. In this study, deleting the orf02889 (AraC-like transcription factor) gene in virulent Aeromonas hydrophila LP-2 affected several important phenotypes, such as increasing biofilm formation and siderophore production abilities. Moreover, Δorf02889 also significantly decreased the virulence of A. hydrophila and has promising attenuated vaccine potential. To better understand the effects of orf02889 on biological functions, a DIA-based quantitative proteomics method was performed to compare the differentially expressed proteins between Δorf02889 and the wild-type strain in extracellular fractions. The following bioinformatics analysis suggested that ORF02889 may regulate various metabolic pathways, such as quorum sensing and ABC transporter metabolism. Moreover, ten selected genes from the top 10 decreasing abundances in proteomics data were deleted, and their virulence to zebrafish was evaluated, respectively. The results showed that ΔcorC, Δorf00906, and Δorf04042 significantly reduced bacterial virulence. Finally, the following ChIP-PCR assay validated that the promoter of corC was directly regulated by ORF02889. Overall, these results provide insight into the biological function of ORF02889 and demonstrate its inherent regulatory mechanism for the virulence of A. hydrophila.